2021
DOI: 10.3389/fphar.2021.769190
|View full text |Cite
|
Sign up to set email alerts
|

Detecting Critical Functional Ingredients Group and Mechanism of Xuebijing Injection in Treating Sepsis

Abstract: Sepsis is a systemic inflammatory reaction caused by various infectious or noninfectious factors, which can lead to shock, multiple organ dysfunction syndrome, and death. It is one of the common complications and a main cause of death in critically ill patients. At present, the treatments of sepsis are mainly focused on the controlling of inflammatory response and reduction of various organ function damage, including anti-infection, hormones, mechanical ventilation, nutritional support, and traditional Chinese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 171 publications
(269 reference statements)
0
4
0
Order By: Relevance
“…Regulation of PI3K/AKT/mTOR pathway is mediated in the mechanism of apoptosis and autophagy, which has been confirmed in animal experiments [ 60 , 61 ]. According to a recent systemic pharmacological analysis, XBJ can affect sepsis by acting on alterations in a number of genes involved in the PI3K/AKT/mTOR signaling pathway [ 8 , 9 ]. Previous research has found that when applied to sepsis, XBJ blocked the phosphorylation of the PI3K/AKT/mTOR signaling pathway [ 62 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regulation of PI3K/AKT/mTOR pathway is mediated in the mechanism of apoptosis and autophagy, which has been confirmed in animal experiments [ 60 , 61 ]. According to a recent systemic pharmacological analysis, XBJ can affect sepsis by acting on alterations in a number of genes involved in the PI3K/AKT/mTOR signaling pathway [ 8 , 9 ]. Previous research has found that when applied to sepsis, XBJ blocked the phosphorylation of the PI3K/AKT/mTOR signaling pathway [ 62 ].…”
Section: Discussionmentioning
confidence: 99%
“…XBJ acts in both the early and late stages of sepsis by anti-inflammatory, anti-coagulation, immune regulation, vascular endothelial protection, anti-oxidative stress and other mechanisms [ 8 ]. A key response protein target coverage of 90.16% was found in the target association pattern of the phytoconstituents of XBJ with the causative genes of sepsis, demonstrating the dominancy of XBJ in the treatment of sepsis [ 9 ]. However, the underlying therapeutic mechanisms of XBJ on sepsis are still unknown, the specific mechanisms of XBJ in SIMI need to be further investigated.…”
Section: Introductionmentioning
confidence: 99%
“…As the only injection in the TMTFs, XBJ is widely used in clinical practice to treat systemic inflammatory response syndrome and MODS [32][33] . Based on a large amount of clinical evidence, XBJ has significant anti-inflammatory, anti-viral, bacteriostatic, and immune-regulating effects, it has been included in the Diagnosis and Treatment Protocol for COVID-19 (Trial Version 5) to treat COVID-19 patients with severe or even critical illness [34][35] .…”
Section: Clinical Studies Of Tmtfs In the Treatment Of Severe-tocriti...mentioning
confidence: 99%
“…This process has successfully helped analyze the key functional compounds and mechanisms of many prescriptions used in complex diseases [ 10 , 11 ]. For some examples, Wang figured out the key components of Chai-Hu-Shu-Gan-San and decoded the mechanism of treating depression by regulating downstream genes through protein kinase A or C to treat depression after cascade signal changes [ 12 ]; Chen found critical ingredients and mechanisms of Xuebijing injection in treating sepsis synergistically by affecting genes such as TAK1, TNF-α, IL-1β, and MEK1 in the MAPK, NF-κB, PI3K-AKT, Toll-like receptor, and TNF signaling pathways [ 13 ].…”
Section: Introductionmentioning
confidence: 99%